Damping Effect of Insulation on a Liquefied Natural Gas Tank Based on Shaking Table Tests. Issue 6 (26th April 2022) - Luo, Dongyu; Sun, Jiangang; Liu, Chunguang; Cui, Lifu; Wang, Zhen
ABSTRACT: Full-capacity large-scale liquefied natural gas (LNG) tanks comprise a steel inner tank and a concrete outer tank. The space between the walls of these two tanks is filled with expanded perlite and a resilient blanket as an insulation layer. It is well known that interactions between the outer tank, insulation, inner tank, and liquid occur under seismic loads. In this study, to investigate the effect of insulation on an LNG tank, a scale model of the tank was constructed, and shaking table tests were conducted with and without insulation at different liquid levels. A comparison of the displacement, acceleration, and axial strain of the tank walls at different test conditions indicates that the insulation exerts good damping effects on the responses of the inner tank wall. Additionally, it has a certain restraining effect on the acceleration of the outer tank wall. However, its damping effect on the displacement and axial strain of the outer tank wall is negligible; in fact, it can even amplify them. Furthermore, most of the maximum seismic responses occur at the full liquid level, for which the effects of the insulation on the tank are more evident than at other liquid levels.